Mitigating Tumor Recurrence through Mitochondrial Metabolism Inhibition: A Novel NIR Laser-Induced Therapeutic Strategy - Yao Liu; Zujun Que; Tianqi An; Zhipeng Zhang; Jianhui Tian (Biological Procedures Online)
Abstract Tumor recurrence driven by mitochondrial hypermetabolism remains a critical challenge in cancer therapy, as aberrant energy metabolism fuels therapeutic resistance and disease progression. We aimed to develop a multifunctional nanoplatform combining mitochondrial metabolism inhibition, photothermal therapy, and controlled chemotherapy to overcome tumor recurrence mechanisms. Biodegradable polydopamine nanoparticles (PDA-DOX-CO NPs) were engineered via molecular self-assembly, co-loading doxorubicin (DOX) and a carbon monoxide (CO) prodrug. The PDA-DOX-CO NPs demonstrated three synergistic therapeutic effects: (1) Photothermal ablation (48.38 °C tumor hyperthermia), (2) CO-mediated mitochondrial suppression, and (3) Spatiotemporally controlled DOX release. In HCT-116 tumor models, PDA-DOX-CO NPs with NIR irradiation induced 60% tumor complete ablation. Histopathological analysis confirmed significant apoptosis induction and mitochondrial morphology alterations in treated tumors. This “metabolic blockade + energy depletion + precision delivery” paradigm provides a synergistic solution to tumor recurrence, demonstrating enhanced therapeutic efficacy and biosafety through mitochondrial-targeted multimodal action.